INCREASE OF THE WHICH HAD MAXIMUM FORCE TO THE TRAINING OF I ROW IN GIG (Fiep Bulletin - online, 2015)
Remo is a sport of races of boats of manual propulsion where each remador uses one or two remos to obtain a support in the water and to stimulate the boat ahead or and reverse speed. Remo in Gig, as well as Remo Olímpico, is a sport of cyclical characteristics of aeróbica-anaeróbica predominance (80-20% respectively (FISA, 2002)) e practised for military of the Navy of Brazil the centuries and currently also for civilians who are part of teams of I row Olímpico. So that remadores obtain to generate big power possible for big time possible, it is necessary that they present beyond a anaeróbico threshold very raised, that allows the work in high intensity for a period of bigger time, one high level of located muscular resistance. The dynamic maximum force is a maximum repetition that can be raised or looser, where has alternation between the concentrical and eccentric contractions (Uchida, Charro, Bacurau, Navarrese and Bridges, 2003). Remo is part of the group of sports where the applications of forces are continuous and high, however is not maximum. When adding the duration of the force applications during a test of I row, more observes a value for return of 1 minute or. Although such fact, is observed an increase of the muscular force of the athletes of I row in Gig. This comment took the achievement of this study that it intended to evaluate the probability of profit in the maximum force in result of the training of I row in gig. The citizens of the study had been 13 athletes of row in gig of the team of the instruction center alexandrino admiral, in the etária band of 23 the 29 years and that they were training for competitions of 1000 meters of distance. the individuals had been submitted the maximum load test in May of 2005 and another one in October of 2005, with the following exercises; rowed seated in the pulley low; rowed bending supported in the bank; pulled for the front in the high pulley and supino rectum in the bank with bar bell of long bar. After the analysis with inferencial statistics (teste_t) was evidenced that the group of citizens carried through at as the moment, October of 2005, test with superior load what it made it in May. Beyond the biggest load, the mapeado increase statistical revealed significantly bigger (p
Keywords: I row in Gig; Test of 1 RM; Training